Impact of Land Tenure System on Socio-Economic Characteristics in Selected Areas of Mymensingh - Haque, Z; Jinan, T (Journal of Environmental Science and Natural Resources, 2018)
The present study aims at investigating into the existing land tenure system of Dorirampur, Jhairpar and Goisa para at Traishal Upazila of Mymensingh District. Keeping in view the objectives 70 samples were randomly selected. Survey method was followed to collect required data. Sampled farmers belonged to six tenurial groups. Out of 70 respondents 34, 22, 16, 7, 10 and 11 percent of total were owner operators, part operators, part tenants, part operator-cum-part tenants, tenants and absentee landowners respectively during the study year. In the study, out of 70 respondents 67 percent were owner operator, 33 percent of them were tenant operators. The selected farmers in the study area practiced three types of share cropping system: i) fifty-fifty share cropping, ii) forty-sixty share cropping and iii) fixed amount of paddy payment. The average annual income were found to be Tk. 97096, 128267, 5215, 76340, 35871 and 113563 respectively for owner operator, part operators, part tenants, part operator-cum-part tenants, tenants and absentee landowner. Analysis of annual income reveals a positive relationship between tenure category and that of annual income during the study area. J. Environ. Sci. & Natural Resources, 10(2): 133-142 2017